Ischaemia‐induced muscle metabolic abnormalities are poorly alleviated by endurance training in a mouse model of sickle cell disease. Issue 3 (15th January 2019) - Chatel, Benjamin; Messonnier, Laurent A.; Vilmen, Christophe; Bernard, Monique; Pialoux, Vincent; Bendahan, David
Abstract : New Findings: What is the central question of this study? The aim of this study was to evaluate the potential beneficial effects of endurance training during an ischaemia–reperfusion protocol in a mouse model of sickle cell disease (SCD). What is the main finding and its importance? Endurance training did not reverse the metabolic defects induced by a simulated vaso‐occlusive crisis in SCD mice, with regard to intramuscular acidosis, mitochondrial dysfunction or anatomical properties. Our results suggest that endurance training would reduce the number of vaso‐occlusive crises rather than the complications related to vaso‐occlusive crises. Abstract: The aim of this study was to investigate whether endurance training could limit the abnormalities described in a mouse model of sickle cell disease (SCD) in response to an ischaemia–reperfusion (I/R) protocol. Ten sedentary (HbSS‐SED) and nine endurance‐trained (HbSS‐END) SCD mice were submitted to a standardized protocol of I/R of the leg, during which ATP, phosphocreatine and inorganic phosphate concentrations and intramuscular pH were measured using magnetic resonance spectroscopy. Forty‐eight hours later, skeletal muscles were harvested. Oxidative stress markers were then measured. Although the time course of protons accumulation was slightly different between trained and sedentary mice ( P < 0.05), the extent of acidosis was similar at the end of the ischaemic period. The initial rate of phosphocreatine resynthesis measured at blood flow restoration, illustrating mitochondrial function, was not altered in trained mice compared with sedentary mice. Although several oxidative stress markers were not different between groups ( P > 0.05), the I/R‐related increase of uric acid concentration observed in sedentary SCD mice ( P < 0.05) was not present in the trained group. The spleen weight, generally used as a marker of the severity of the disease, was not different between groups ( P > 0.05). In conclusion, endurance training did not limit the metabolic consequences of an I/R protocol in skeletal muscle of SCD mice, suggesting that the reduction in the severity of the disease previously demonstrated in the basal state would be attributable to a reduction of the occurrence of vaso‐occlusive crises rather than a decrease of the deleterious effects of vaso‐occlusive crises. Abstract :